Personal protective equipment use during industrial hog operation work activities and acute lung function changes in a prospective worker cohort, North Carolina 2014–2015. Issue 8 (6th June 2021) - Coffman, Vanessa R.; Hall, Devon J.; Pisanic, Nora; Nadimpalli, Maya; McCormack, Meredith; Diener‐West, Marie; Davis, Meghan F.; Heaney, Christopher D.
Abstract: Introduction: Occupational activities related to industrial hog operation (IHO) worker lung function are not well defined. Therefore, we aimed to identify IHO work activities associated with diminished respiratory function and the effectiveness, if any, of personal protective equipment (PPE) use on IHOs. Methods: From 2014 to 2015, 103 IHO workers were enrolled and followed for 16 weeks. At each biweekly visit, work activities and PPE use were self‐reported via questionnaire and lung function measurements were collected via spirometry. Generalized linear and linear fixed‐effects models were fitted to cross‐sectional and longitudinal data. Results: Increasing years worked on an IHO were associated with diminished lung function, but baseline and longitudinal work activities were largely inconsistent in direction and magnitude. Unexpectedly, a −0.3 L (95% confidence interval: −0.6, −0.04) difference in forced expiratory volume in the first second (FEV1 ) was estimated when workers wore PPE consistently (≥80% of the time at work) versus those weeks they did not. In post‐hoc analyses, we found that coveralls and facemasks were worn less consistently when workers experienced worse barn conditions and had more contact with pigs, but coveralls were worn more consistently as cleaning activities increased. Conclusions: Similar to past studies, baseline estimates were likely obscured by healthy worker effect bias, but showed decrements in worker lung function as years of work increased. A challenge to disentangling the effect of work activities on lung function was the discovery that IHO workers used PPE differently according to the work task. These data suggest that interventions may be targeted toward improving barn conditions so that workers can consistently utilize IHO‐provided PPE.